Curb your enthusiasm. The complete third season [videorecording (DVD)] - David, Larry (Home Box Office, 2005)
Larry David has a charmed life - success, famous friends, a patient wife, a dedicated manager and a trendy new restaurant ... so what's his problem? . Includes all 10 episodes from this Emmy award-winning season.